2024
DOI: 10.1001/jamasurg.2023.6374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Traumatic Brain Injury and Exposure to Extracranial Surgery

Christopher J. Roberts,
Jason Barber,
Nancy R. Temkin
et al.

Abstract: ImportanceTraumatic brain injury (TBI) is associated with persistent functional and cognitive deficits, which may be susceptible to secondary insults. The implications of exposure to surgery and anesthesia after TBI warrant investigation, given that surgery has been associated with neurocognitive disorders.ObjectiveTo examine whether exposure to extracranial (EC) surgery and anesthesia is related to worse functional and cognitive outcomes after TBI.Design, Setting, and ParticipantsThis study was a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…However, it is difficult to disentangle the effects of systemic injuries from those of brain injuries in clinical practice. 27 Roberts et al 28 found a correlation between extracranial surgery and anesthesia with adverse functional outcomes and impaired executive function following TBI. Nevertheless, it is vital to identify patients with lower extremity injuries and ensure that proper treatment options are available, regardless of the time of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to disentangle the effects of systemic injuries from those of brain injuries in clinical practice. 27 Roberts et al 28 found a correlation between extracranial surgery and anesthesia with adverse functional outcomes and impaired executive function following TBI. Nevertheless, it is vital to identify patients with lower extremity injuries and ensure that proper treatment options are available, regardless of the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Other factors such as surgical urgency, 30 insults introduced intraoperatively or during transportation, and other factors that may affect the results were not considered in our analysis. 28 Patients with severe TBI (GCS score <8) are more likely to experience secondary insults (eg, hypotension, intraoperative bleeding, hypoxia, hyperventilation, and increase in ICP) due to lying flat on the operating table; these patients are least likely to benefit from early ambulation and shorter bed rest. For patients with moderate to severe TBI, early fixation may increase the risk of secondary insult, suggesting that there is no need to expedite extremity fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The initial severity of TBI was usually classified as mild, moderate, or severe based on the clinical awareness level of the Glasgow Coma Scale (GCS) [ 5 ]. The GCS score, together with age, computed tomography (CT) findings, hypoxia, and systolic blood pressure are the significant factors affecting the prognosis [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging and neurodegenerative related diseases, such as Alzheimer's disease (AD) and some cerebrovascular diseases, exhibit increased vulnerability to postoperative neurocognitive disorders (PND), which affects millions of surgical patients every year (Silbert et al, 2015;Li et al, 2021;Sun et al, 2021;Roberts et al, 2024). PND is characterized by a surgery-induced deterioration in cognitive function, including memory impairment, attention deficits, and other cognitive domain impairments.…”
Section: Introductionmentioning
confidence: 99%